Effect of LINC00657 on Apoptosis of Breast Cancer Cells by Regulating miR-590-3p - Shan Q (Cancer Management and Research, 2020)
Qiuli Shan,1 Fan Qu,1 Weiping Yang,2 Ningning Chen1 1College of Biological Science and Technology, University of Jinan, Jinan 250022, People’s Republic of China; 2Department of Thyroid Breast Surgery, Qingdao Chengyang People’s Hospital, Qingdao, People’s Republic of ChinaCorrespondence: Qiuli ShanCollege of Biological Science and Technology, University of Jinan, No. 336, Nanxinzhuan West Road, Jinan, Shandong Province 250022, People’s Republic of ChinaTel +86-18753151252Email bio_shanql@ujn.edu.cnObjective: To investigate the effect of LINC00657 on breast carcinoma by regulating miR-590-3p.Methods: Ninety-seven cases with breast carcinoma who were admitted to Qingdao Chengyang People’s Hospital were collected. The breast carcinoma (n=97) and tumor-adjacent tissues (n=97) of patients were collected during the operation with the permission of the patients. The expressions of LINC00657 and miR-590-3p were detected in breast carcinoma cells and tissues. The breast carcinoma cells were transfected and their proliferation, migration, invasion and apoptosis were detected.Results: LINC00657 was highly expressed in breast carcinoma tissues, while miR-590-3p was reduced (P< 0.05). The proliferation, invasion and migration of cells transfected with si-LINC00657 or miR-590-3p-mimics were significantly inhibited, and the apoptosis rate increased, resulting in the up-regulation of the expressions of apoptosis-related proteins Bax and Caspase-3 and the reduction of Bcl-2 (P< 0.05). After si-LINC00657 or miR-590-3p-mimics, the level of GOLPH3 decreased. Through double luciferase report and RIP experiment, it was confirmed that LINC00657 could act as a sponge of miR-590-3p to negatively regulate its expression. After correlation analysis, it was concluded that there was a negative correlation between LINC00657 and miR-590-3p. Rescue experiments concluded that co-transfection of si-LINC00657+miR-590-3P-inhibitor could reverse the inhibitory action of si-LINC00657 on breast carcinoma cells.Conclusion: LINC00657 can participate in the biological behavior process of breast carcinoma by regulating miR-590-3p/GOLPH3 signal.Keywords: LINC00657, miR-590-3p, GOLPH3, breast carcinoma, apoptosis